QUALITATIVE PHYTOCHEMICAL SCREENING, GC-MS ANALYSIS AND ANTIBACTERIAL ACTIVITY OF PALMYRA FRUIT PULP (Borassus flabellifer L.) - B.VIJAYAKUMARI; P.C.VENGAIAH; P.KIRANMAYI (International Journal of Pharma and Bio Sciences, 2015)
This study report the phytochemicals present in ethanolic extract of palmyra fruit pulp (PFP). Phytochemical screening of fruit pulp extract revealed the presence of saponins, flavonoids, phenolic compounds and glycosides. The extract was analyzed by Gas Chromatography-Mass Spectrometry (GC-MS) and 10 different compounds were identified. Well diffusion method was employed to determine the effect of antibacterial potential against Gram positive bacteria i.e., Staphylococcus aureus, Gram negative bacteria i.e., Escherichia coli.